(untitled) (Research, Society and Development, 2022)
Ananas comosus var. erectifolius is a bromeliad native of the Amazon Complex has aroused great interest of the industries due to a softness, strength and low density of fibers extracted from its leaves. The frequent demand and effective protocols for in vitro regeneration and establishment of species, of commercial and environmental interest, encourages studies of organogenesis induced by growth regulators. The rhizogenesis or in vitro rooting is the last step of the regeneration process and is often considered the greatest challenge to be overcome. Rhizogenesis of Ananas comosus var. erectifolius was evaluated under the influence of the growth regulators naphthalene acetic acid (NAA) and indole butyric acid (IBA). Seven experiments were performed using different concentrations of growth regulators on solid MS medium under controlled environmental conditions. The results will improve the laboratorial protocols of induction, multiplication, elongation and production of root biomass for A. comosus var. erectifolius. The in vitro rooting was feasible and better results were observed using 1.0 mg L-1 NAA + 1.0 mg L-1 IBA.